Răspuns :
(x-3)(y+4)=12
12=4x3
12=3x4
12=12x1
12=6x2
12=2x6
1. x-3=2
x=3+2
x=5
y+4=6
y=6-4
y=2
2..x-3=3
x=3+3
x=6
y+4=4
y=4-4
y=0
3.. x-3=1
x=3+1
x=4
y+4=12
y=12-4
y=8
12=4x3
12=3x4
12=12x1
12=6x2
12=2x6
1. x-3=2
x=3+2
x=5
y+4=6
y=6-4
y=2
2..x-3=3
x=3+3
x=6
y+4=4
y=4-4
y=0
3.. x-3=1
x=3+1
x=4
y+4=12
y=12-4
y=8
(x-3)(y+4)=12
xy+4x-3y-12=12
xy+4x-3y-24=0
(x-3)y=24-4x
x-3≠0
y=[-4(x-6)]/(x-3)
Cind x=4, y=8
x=5, y=2
x=6, y=0
x=7, y=-1
xy+4x-3y-12=12
xy+4x-3y-24=0
(x-3)y=24-4x
x-3≠0
y=[-4(x-6)]/(x-3)
Cind x=4, y=8
x=5, y=2
x=6, y=0
x=7, y=-1